House physical environment and incidence of acute respiratory tract infection: Regression test logistics for toddlers - Herawati, Cucu; Amalia, Shulha (Science, Engineering and Health Studies, 2025)
Acute respiratory tract infection (ARI) is a highly contagious disease, particularly among toddlers. The risk factors associated with this disease include environmental conditions, physical factors, and living in unhealthy house. Therefore, this study aimed to examine the environmental and physical characteristics of households in correlation with the incidence of ARI among toddlers. The method adopted was a quantitative cross-sectional design. A total sample of 91 was selected using a simple random sampling method. Data were collected through interviews and measurements, and the analysis was conducted using multivariate analysis and logistic regression testing. The results showed a significant relationship between lighting, humidity, and room temperature with the incidence of ARI. The most related variable was humidity. Respondents who resided in humid houses that did not meet the recommended conditions were more than 15 times as likely to be infected with ARI.